Contribution of gut microbiomes and their metabolomes to the performance of Dorper and Tan sheep - Ma, Yuhao; Yang, Xue; Hua, Guoying; Deng, Xiaotian; Xia, Tianlan; Li, Xinhai; Feng, Dengzhen; Deng, Xuemei (Frontiers in Microbiology, 2022)
Livestock is an excellent source of high nutritional value protein for humans; breeding livestock is focused on improving meat productivity and quality. Dorper sheep is a distinguished breed with an excellent growth performance, while Tan sheep is a Chinese local breed famous for its delicious meat. Several studies have demonstrated that the composition of gut microbiome and metabolome modulate host phenotype. In the present study, we performed 16S amplicon sequencing and metabolomic analyses of the rumen and hindgut microbiome of 8-month-old Dorper and Tan sheep, raised under identical feeding and management conditions, to explore the potential effects of gut microbiome and its metabolites on growth performance and meat quality. Our study identified Lactobacillus, a marker genus in the rumen, to be significantly associated with the levels of fumaric acid, nicotinic acid, and 2-deoxyadenosine (P-value <0.05). Statistical analysis showed that nicotinic acid was significantly negatively correlated with body weight (P-value <0.01), while 2-deoxyadenosine was significantly positively correlated with fatty acids content (P-value <0.05). There was a biologically significant negative correlation between Phascolarctobacterium and deoxycytidine levels in the hindgut. Deoxycytidine was significantly positively correlated with body weight, protein and amino acid content. Differences in rumen fermentation patterns that are distinctive among breeds were identified. Tan sheep mainly used Lactobacillus and fumaric acid-mediated pyruvic acid for energy supply, while Dorper sheep utilize glycogenic amino acids. The difference of iron metabolism in the hindgut of Dorper sheep affects lipid production, while Phascolarctobacterium in Tan sheep is related to roughage tolerance. The accumulation of nucleosides promotes the growth performance of Dorper sheep. These findings provide insights into how the microbiome–metabolome-dependent mechanisms contribute to growth rate and fat contents in different breeds. This fundamental research is vital to identifying the dominant traits of breeds, improving growth rate and meat quality, and establishing principles for precision feeding.